Open Source Digital Health Software for Resilient, Accessible and Equitable Healthcare Systems - Paton, Chris; Braa, Jørn; Muhire, Andrew; Marco-Ruiz, Luis; Kobayashi, Shinji; Fraser, Hamish; Falcón, Luis; Marcelo, Alvin (Yearbook of Medical Informatics, 2022)
Objective: To assess the impact of open-source projects on making healthcare systems more resilient, accessible and equitable.Methods: In response to the International Medical Informatics Association (IMIA) call for working group contributions for the IMIA Yearbook, the Open Source Working Group (OSWG) conducted a rapid review of current open source digital health projects to illustrate how they can contribute to making healthcare systems more resilient, accessible and equitable. We sought case studies from the OSWG membership to illustrate these three concepts and how open source software (OSS) addresses these concepts in the real world. These case studies are discussed against the background of literature identified through the rapid review.Results: To illustrate the concept of resilience, we present case studies from the adoption of District Health Information Software version 2 (DHIS2) for managing the Covid pandemic in Rwanda, and the adoption of the OpenEHR open Health IT standard. To illustrate accessibility, we show how open source design systems for user interface design have been used by governments to ensure accessibility of digital health services for patients and healthy individuals, and by the OpenMRS community to standardise their user interface design. Finally, to illustrate the concept of equity, we describe the OpenWHO framework and two open source digital health projects, GNU Health and openIMIS, that both aim to reduce health inequities through the use of open source digital health software.Conclusion: This review has demonstrated that open source software addresses many of the challenges involved in making healthcare more accessible, equitable and resilient in high and low income settings.
Keywords: Open source software; health system; resilience; accessibility; equity